2013
DOI: 10.1259/dmfr.20130145
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of cone beam CT and micro-CT on trabecular bone structures in the human mandible

Abstract: The present study demonstrated the potential of high-resolution CBCT imaging for in vivo applications of quantitative bone morphometry and bone quality assessment. However, the overestimation of morphometric parameters and acquisition settings in CBCT must be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 19 publications
1
69
0
4
Order By: Relevance
“…Although several authors have found a correlation between bone quantity and bone structure parameters on CBCT and mCT or dual-energy X-ray absorptiometry images ( Figure 5), 57,85,[93][94][95] the limitations to the use of correlation analysis mentioned above apply here as well. To consider these parameters for clinical use, a very high correlation would need to be demonstrated, as well as stable inter-and intra-CBCT values (i.e.…”
Section: Alternative Methods For Bone Evaluationmentioning
confidence: 78%
“…Although several authors have found a correlation between bone quantity and bone structure parameters on CBCT and mCT or dual-energy X-ray absorptiometry images ( Figure 5), 57,85,[93][94][95] the limitations to the use of correlation analysis mentioned above apply here as well. To consider these parameters for clinical use, a very high correlation would need to be demonstrated, as well as stable inter-and intra-CBCT values (i.e.…”
Section: Alternative Methods For Bone Evaluationmentioning
confidence: 78%
“…Secondly, a high correlation does not imply that the numerical values correspond between the two variables, and large differences between bone parameter values of CBCT and other modalities have been revealed. [27][28][29][30][31] As seen in Table 1, correlation coefficients could be reasonably high even if the values for CBCT were severely underor overestimated (as shown by the calibration coefficients). In other words, even if a bone parameter is found to have a high correlation coefficient, the value obtained from CBCT images may be far off the true value.…”
Section: Discussionmentioning
confidence: 92%
“…[23][24][25][26] Various other studies have measured morphometric and other parameters, correlating values from CBCT with those from mCT and dual-energy X-ray absorptiometry. [27][28][29][30][31] Correlation coefficients were typically interpreted as "high". However, when comparing the present results with previous studies, it is important to note that a correlation coefficient has limited value when evaluating the potential clinical applications of these bone parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Prior investigations have shown varying degrees of variability for a subset of bone structure parameters as a result of varying scan settings. 10,14,15 However, to our knowledge, an analysis of all available bone structure parameters on a larger (n . 8) sample has not yet been performed.…”
Section: Introductionmentioning
confidence: 98%